A SURVEY OF SECURED VOTING SYSTEM USING FINGERPRINT SCANNER - Hyvallika, B.; Ganapathy, Kirupa (International Journal of Psychosocial Rehabilitation, 2020)
HE main objective of this project is to avoid the false entry of the voters in the election process. Voting can be done at home by using fingerprint scanner method. The main idea of this project is to provide secure methods of voting through the fingerprint scanner. The election process is mandatory in the world. To develop the voting system based on the finger print acceptance of the voters with the program uploaded in the Arduino. By using the present voting system, it takes more time for the remaining voters to vote as it is necessary to avoid the chaos. Therefore, results in casting less number of votes. Validation of voters become incorrect during this process. People inside the election booth and third person entry may result in false count of voters. Normally elections are conducted for the Indian constitution and parliamentary legislation. This paper discusses different voting techniques and the issues faced there by suggesting techniques to overcome.